HUBUNGAN KOMUNIKASI INFORMASI DAN EDUKASI (KIE) TENTANG DISMENOREA DENGAN TINGKAT NYERI PADA REMAJA YANG MENGALAMI MENSTRUASI DIDESA BINJAI DUSUN V TEBING SYAHBANDAR TAHUN 2022 - Purba, Tetty Junita; Siregar, GF Gustina; Meliyana, Cindy (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
Adolescence in women is a period of physical and psychological preparation to become a mother in the future. Communication, Information and Education (IEC) is a process of conveying messages, information provided to the community Both Using media such as: radio, television, press, film, etc. Gynecological disorders that often occur in adolescents are disorders related to the menstrual cycle. Some of these are dysmenorrhoea and Pre Menstrual Syndrome (PMS). During menstruation, each woman has a different experience where some of them experience discomfort in the pelvis or painDysmenorrhea can be defined as a medical condition that occurs during menstruation that can interfere with activity and requires treatment characterized by pain or pain in the abdominal or pelvic area. Menstruation is the bleeding of the uterus along with the release of the endometrium that takes place periodically and cyclically. The study used a pre-experimental design with a one- group pre-post test design. Population and Sample In this study there were 20 people with a total sampling technique. Based on the results of the study, p= 0.002 or p ≤ 0.05 means that there is a relationship between ME Dysmenorrhea and the level of menstrual pain in adolescents in binjai village, hamlet V tebing syahbandar in 2022.